Những câu hỏi liên quan
Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
25 tháng 12 2018 lúc 17:42

a) (x - y)(x + y + 3).                    b) (x + y - 2xy)(2 + y + 2xy).

c) x 2 (x + l)( x 3  -  x 2  + 2).              d) (x – 1 - y)[ ( x   -   1 ) 2   +   ( x   -   1 ) y   +   y 2 ].

Bình luận (0)
Trần Đức Anh
Xem chi tiết
Minh Nguyễn
1 tháng 10 2021 lúc 8:04

1/(x+2)-(3x-1)2=(x+2+3x-1)(x+2-3x+1)=4x(-2x+3)=-8x2+12x

2/(x4+x2)(-2x3-2x)=x2(x2+1)-2x(x2+1)=(x2+1)(x2-2x)

Bình luận (0)
tràn nhân quang
Xem chi tiết
Nguyễn Hoàng Minh
30 tháng 11 2021 lúc 9:40

\(=x\left(2x^2+3x-2\right)=x\left(2x^2+4x-x-2\right)=x\left[2x\left(x+2\right)-\left(x+2\right)\right]=x\left(2x-1\right)\left(x+2\right)\)

Bình luận (0)
Lily Nguyễn
30 tháng 11 2021 lúc 9:52

2x3 + 3x2 - 2x

= x ( 2x2 + 3x - 2 )

= x ( 2\(x^2\) + 4\(x-x-2\) )

= x [ ( 2\(x^2\) + 4x ) - ( x + 2 )]

= x  [  2x ( x + 2 ) - ( x + 2 )]

= x ( 2x - 1 ) ( x + 2 )

Bình luận (0)
Dung Vu
Xem chi tiết
Lấp La Lấp Lánh
7 tháng 11 2021 lúc 10:43

1a) \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)

b) \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)

Bình luận (0)
Nguyễn Hoàng Minh
7 tháng 11 2021 lúc 10:43

\(a,=-\left(x-1\right)^3\left[=\left(1-x\right)^3\right]\\ b,=\left(1-x\right)^3\)

Bình luận (1)
ILoveMath
7 tháng 11 2021 lúc 10:43

a. \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)

b. \(=\left(1-x\right)^3\)

Bình luận (0)
Nguyễn Thị Hải Yến
Xem chi tiết
alibaba nguyễn
21 tháng 8 2016 lúc 22:24

Đề yêu cầu làm gì bạn

Bình luận (0)
alibaba nguyễn
22 tháng 8 2016 lúc 22:46

\(\frac{\left(a-b\right)^2}{4}\)- 1 = (\(\frac{a-b}{2}\)- 1)(\(\frac{a-b}{2}\)+ 1)

Bình luận (0)
Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
17 tháng 2 2018 lúc 18:06

x3 + 3x2 + 3x + 1 = x3 + 3x2.1 + 3x.12 + 13 = (x + 1)3

Bình luận (0)
hoa tran
Xem chi tiết
ILoveMath
30 tháng 10 2021 lúc 14:57

1/\(=a\left(a-b\right)+\left(a-b\right)=\left(a-b\right)\left(a+1\right)\)

2/ \(=\left(x^2-2x+1\right)-y^2=\left(x-1\right)^2-y^2=\left(x-y-1\right)\left(x+y-1\right)\)

Bình luận (0)
Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
5 tháng 3 2018 lúc 3:31

d) x3 + 3x2 – 3x – 1

= (x3 - 1) + (3x2 - 3x)

= (x - 1)(x2 + x + z) + 3x(x - 1)

= (x - 1)(x2 + 4x + 1)

Bình luận (0)
Pham Trong Bach
Xem chi tiết
Cao Minh Tâm
31 tháng 3 2018 lúc 7:00

a) x3 + 3x2 – 3x – 9

= (x3 + 3x2) - (3x + 9)

= x2(x + 3) - 3(x + 3)

= (x + 3)(x2 - 3)

= (x + 3)(x + √3)(x - √3)

Bình luận (0)